Molecular Analysis and Genome Discovery. - Rapley, Ralph (John Wiley & Sons, 2011)
Molecular Analysis and Genome Discovery, Second Edition is a completely revised and updated new edition of this successful book. The text provides a comprehensive overview of recent developments in the fast moving field of molecular based diagnostics of disease markers. Key concepts and applications are provided alongside practical information on current techniques currently being researched and developed. Each chapter offers an up-to-date analysis of the subject encompassing the very latest technology platforms and is an essential reference for researchers in the field looking for an u.